Fentanyl Versus Lidocaine Intravenously to Attenuate Hemodynamic Effects of En-dotracheal Intubation - Hozan Abdulwahid Ahmed; Amir Murad Khudadad Boujan; Othman Ismat Abdulmajeed (Advanced Medical Journal)
Background and objectives:Hemodynamic changes to laryngoscopy and endotracheal intubation may increase mor- bidity in the perioperative period. Those changes may become significant in patients with uncontrolled hypertension or heart diseases. In this study, we compared the efficacy of intravenous fentanyl and intravenous lidocaine in attenuating the hemodynamic responses during laryngoscopy and intubation.